Multicenter International Society for Immunotherapy of Cancer Study of the Consensus Immunoscore for the Prediction of Survival and Response to Chemotherapy in Stage III Colon Cancer - Mlecnik, Bernhard; Bifulco, Carlo; Bindea, Gabriela; Marliot, Florence; Lugli, Alessandro; Lee, J Jack; Zlobec, Inti; Rau, Tilman T; Berger, Martin D; Nagtegaal, Iris D; Vink-Börger, Elisa; Hartmann, Arndt; et al. (Journal of clinical oncology, 2020)
PURPOSE: The purpose of this study was to evaluate the prognostic value of Immunoscore in patients with stage III colon cancer (CC) and to analyze its association with the effect of chemotherapy on time to recurrence (TTR). METHODS: An international study led by the Society for Immunotherapy of Cancer evaluated the predefined consensus Immunoscore in 763 patients with American Joint Committee on Cancer/Union for International Cancer Control TNM stage III CC from cohort 1 (Canada/United States) and cohort 2 (Europe/Asia). CD3+ and cytotoxic CD8+ T lymphocyte densities were quantified in the tumor and invasive margin by digital pathology. The primary end point was TTR. Secondary end points were overall survival (OS), disease-free survival (DFS), prognosis in microsatellite stable (MSS) status, and predictive value of efficacy of chemotherapy. RESULTS: Patients with a high Immunoscore presented with the lowest risk of recurrence, in both cohorts. Recurrence-free rates at 3 years were 56.9% (95% CI, 50.3% to 64.4%), 65.9% (95% CI, 60.8% to 71.4%), and 76.4% (95% CI, 69.3% to 84.3%) in patients with low, intermediate, and high immunoscores, respectively (hazard ratio [HR; high v low], 0.48; 95% CI, 0.32 to 0.71; P = .0003). Patients with high Immunoscore showed significant association with prolonged TTR, OS, and DFS (all P < .001). In Cox multivariable analysis stratified by participating center, Immunoscore association with TTR was independent (HR [high v low], 0.41; 95% CI, 0.25 to 0.67; P = .0003) of patient's sex, T stage, N stage, sidedness, and microsatellite instability status. Significant association of a high Immunoscore with prolonged TTR was also found among MSS patients (HR [high v low], 0.36; 95% CI, 0.21 to 0.62; P = .0003). Immunoscore had the strongest contribution χ2 proportion for influencing survival (TTR and OS). Chemotherapy was significantly associated with survival in the high-Immunoscore group for both low-risk (HR [chemotherapy v no chemotherapy], 0.42; 95% CI, 0.25 to 0.71; P = .0011) and high-risk (HR [chemotherapy v no chemotherapy], 0.5; 95% CI, 0.33 to 0.77; P = .0015) patients, in contrast to the low-Immunoscore group (P > .12). CONCLUSION: This study shows that a high Immunoscore significantly associated with prolonged survival in stage III CC. Our findings suggest that patients with a high Immunoscore will benefit the most from chemotherapy in terms of recurrence risk.
Keywords: CD3 Complex; Disease-Free Survival; Male; mutace; protinádorové látky; Microsatellite Instability; Survival Rate; lokální recidiva nádoru; Chemotherapy, Adjuvant; Lymphocytes, Tumor-Infiltrating; Neoplasm Staging; mikrosatelitní nestabilita; antigeny CD3; počet lymfocytů; Aged; mužské pohlaví; senioři; CD8-Positive T-Lymphocytes; Antineoplastic Agents; Time Factors; Neoplasm Recurrence, Local; senioři nad 80 let; Lymphocyte Count; lidé; CD8-pozitivní T-lymfocyty; ženské pohlaví; Humans; časové faktory; Colonic Neoplasms; Aged, 80 and over; prediktivní hodnota testů; nádory tračníku; adjuvantní chemoterapie; Mutation; Female; tumor infiltrující lymfocyty; lidé středního věku; staging nádorů; Predictive Value of Tests; přežití bez známek nemoci; míra přežití; Middle Aged